Wachstumsfolgen von Einkommensungleichheit: Theorie, empirische Evidenz und Politikempfehlungen - Jochen Hartwig (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2018)
– Income inequality is "the defining challenge of our time", former US President Barack Obama said in a speech in December 2013. Undoubtedly, the financial crisis and the sluggish recovery in its aftermath have increased the attention to rising inequality. This survey addresses the consequences of income inequality for economic growth from a theoretical and from an empirical angle. Both perspectives yield inconclusive results on whether inequality is "good" or "bad" for growth. This poses a problem for policymakers contemplating (e.g. tax) policies aimed at raising or lowering inequality. On the other hand, policies to promote social justice arguably do not need to pass a "do they increase economic growth?" test. Some policy proposals which would reduce inequality are discussed as well.
Keywords: E25; E61; E62; E64; O49; 330; Income distribution; economic growth; economic policy